(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
THE POBOCZNA GATE AT THE CRACOW FORTIFICATIONS The Poboczna gate at the foot of Wawel Hill leading towards Zwierzyniec, was erected c. 1340, together with defensive walls which linked the chartered city with the castle. Initially the tower probably bore the name „Zwierzyniecka” or „Grodzka”; at the end of the 14th century it was referred to as the „porta Dimitrij”, as it neighboured the manor of Dymitr of Goraj. It was also described as leading „to the Vistula”. Finally, in the second half of the 16th century it began to be called the Poboczna (sideway) Gate. The last of the names should not be associated with a minor role, but rather with the site to which the road out of this gate led; it was Poboczna Island, situated in Zwierzyniec at the mouth of the Rudawa River at the Vistula River. Iconography and maps do not permit accurate reconstruction of the appaearance and location of the medieval gate, which was destroyed during the reign of August II in the beginning of the 18th century. It was probably reconstructed c. 1740, without defensive features. It survived in this shape until 1822, when it was finally demolished. Exavation work may give answered to the question of the precise location of this structure.